Opportunities and Challenges of Muslim-Friendly Tourism in the Mandeh Island Tourism Area - Mandalia, Siska (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
The emergence of Muslim-friendly tourism as a significant trend in the global tourism industry has gained significant traction due to the rising number of Muslim travelers seeking destinations that align with their religious and cultural values. Mandeh Island in West Sumatra Province, Indonesia, renowned for its stunning natural beauty, has begun to focus on developing Muslim-friendly tourism. This study examines the opportunities and challenges associated with creating this type of tourism in the Mandeh Island tourism area, utilizing the Global Muslim Travel Index (GMTI) indicators as a framework. The research findings highlight the considerable potential of Mandeh Island to attract Muslim travelers owing to its captivating landscapes and relatively preserved environment. Access, Communication, Environment, Facilities, and services adhering to Islamic principles have begun to be established, including alcohol-free accommodation, prayer areas, and halal dining options. However, challenges such as the need for enhanced infrastructure, limited accessibility, and local awareness of the needs of Muslim travelers still impact their overall experience. Effective marketing communication is also essential to reaching the global market of Muslim tourists. Consequently, this study concludes that while Mandeh Island holds substantial potential for Muslim-friendly tourism, collaborative efforts involving the government, private sector, and local communities are essential to address the existing challenges and maximize the available opportunities. This research contributes to the growing body of knowledge on niche tourism segments and provides practical recommendations for stakeholders in Pulau Mandeh to enhance their offerings and tap into the Muslim-friendly tourism market.